The respiratory diaphragm in osteopathic vision: a literature review - Sagrillo, Luiza Minato; Frigo, Letícia Fernandez (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Considering the osteopatic reasoning, and possible to establish a two-way interaction of direct contact or indirect of the respiratory diaphragm Several abdominal and thoracic viscera, as well as, of your skeletal inserts relations. Objective: This study aimed to investigate how anatomical and physiological relations of the diaphragm in both painful processes of the spine, in bodies Associates. Method: This study was a literature review, with searching online data PubMed, the published articles in the last ten years as associating keywords this study. Results: Ten articles contemplated the criteria for inclusion and exclusion this research and related disorders such as diaphragmatic as possible causes of low back and neck pain, and gastroesophageal reflux disease, as well as, stressed its importance as respiratory-venous-lymphatic pump. Conclusion: The respiratory diaphragm is no link anatomical and physiological interaction between the various body systems, and therefore, may be involved in dysfunctional chains que manifest signs and symptoms and local said. It is involved in several causes of pain on which to observe biomechanical changes in functional or column viscera next or correlated.